PENGARUH RETURN ON ASSET, RETURN ON EQUITY, EARNING PER SHARE DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM - Puteri Alayda Yahya; Dicky Arisudhana (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of return on assets, return on equity, earnings per share, and net profit margin on stock prices. This study used secondary data from a population of 44 companies, specifically nickel mining companies listed on the Indonesia Stock Exchange between 2021 and 2024. Thirteen companies served as the sample for the study, with the observation period of 2021 and 2024. The sampling technique used was purposive sampling with multiple linear regression analysis. The results of this study indicate that return on assets and return on equity have no effect on stock prices, while earnings per share and net profit margin do.